QUALITY ASSESSMENT SERVICE OF DAYCARE LIVING IN JAKARTA - Ariani, Meiliyah; Zulhawati (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
The young mothers of careers who live in metropolis and as people with toddlers especially in Jakarta Capital Special Region, today faces a variety of challenges; one of which is how to take care of their toddlers. In the face of such phenomenon, emerging business activities that offer service programs to take care of children under five with various facilities along with all its limitations. Whether with the emergence of service businesses to take care of children under five especially in metropolis, already provide quality services for customers so feel safe and comfortable to continue their career? To do research of such phenomenon, selected two subjects residing in Jakarta; that are: â€œThe Harvest Daycareâ€ and â€œBaby Kangarooâ€. Is the quality of services provided from both day care is already in "GOOD" category according to its customers so that their satisfaction is fulfilled? This is the main attraction for case study, in order to reveal some important factors in improving the quality of daycare services. Therefore, the satisfaction of young mothers as customers feels a strong spirit and a strong emotional drive to remain committed to their careers. Research is done by taking samples of both daycare customers and the sample amount is 50 (fifty) customers for each. The research design consists of five dimensions of measurement, namely: Tangibles; Reliability; Responsiveness; Assurance and Empathy; up to the measurement indicators of each dimension. Analytical method using quantitative analysis model application with the name â€œTEVâ€. The result of the research is the customers of both day care feel satisfied, so as to provide an assessment that the quality of services of both daycare in the category of â€œGOODâ€. Indicator which assessment needs to be improved again so that service quality can be improved to be â€œVERY GOODâ€ category; then can be read in the conclusions and suggestions chapter of the research report.